SIKAP, KEPUASAN DAN LOYALITAS KONSUMEN SUSU SEGAR YU-ONE MILK DI KOTA BANDAR LAMPUNG - Fitri, Ayu Aulia; Indriani, Yaktiworo; Rufaidah, Erlina (Lampung University, 2024)
This research aims to determine the attitudes, purchasing patterns, satisfaction, and loyalty of fresh milk consumers of Yu-One Milk at Jalan Sultan Agung, Way Halim, Kedaton District of Bandar Lampung City. The research method is a survey. The number of respondents in this research are 60 people, selected by non-probability sampling technique, namely accidental sampling. The research data are analyzed by quantitative descriptively using the Fishbein multi-attribute model, Customer Satisfaction Index (CSI) and the loyalty pyramid. Data collection was carried out in October-November 2022. The results showed that the consumers’ attitude toward multi-attribute of Yu-One Milk fresh milk was in the good category, in which score was 181.72 and the most favored attribute by consumers was friendliness services. Most of Yu-One Milk consumers (25%) bought fresh milk with chocolate flavor variants. The average frequency of purchasing Yu-One Milk fresh milk was twice per month with a purchase expenditure of IDR 51,883.00/month. The average purchases amount of Yu-One Milk fresh milk was 1,377 ml/month with the purpose of purchasing to eliminate hunger/thirst (46.67%). Yu-One Milk fresh milk consumer satisfaction was in the very satisfied category with a CSI value of 83.61. Yu-One Milk consumer loyalty was quite good in the form of an inverted pyramid. The switcher buyer value was 46.67%, the habitual buyer value was 48.83%, the satisfied buyer value was 90.00%, the liking the brand value was 86.67% and the committed buyer value was 83.33%. Keywords: attitude, consumer loyalty, fresh milk, purchase pattern, satisfaction.